A Review on Rural Road Improvement and Its Impact on Socioeconomic Development of Kaski District - Baral, Prakash (Journal of Advanced Academic Research, 2023)
Rural roads are the spinal cord whose connectivity to the settlements, cultivated lands and its improvement play an important role in sustainable socio-economic development of Kaski district as well as developing country like Nepal as a whole. The accessibility of rural road network is reflected in the field of education, health, employment, agriculture, marketing, tourism as well as in the changing pattern of daily livelihood of rural community in Kaski district. There is some level of achievement of fair weather road but is not sufficient regarding to accessibility to remote settlement and productivity. They need to be prioritizing for improvement to all weather road based on productivity. Improvement like upgrading, opening of track, culvert also seems to be necessary which too reflect positive impact on socio-economic development of Kaski district. This paper tries to review 19 district roads under government planning and emphasis for prioritization for upgrading (earthen, gravel, bitumen) based on cost-benefit ratio analysis. Indicators are taken basically on the basis of agriculture, school, health facility, access to market, access to district centre, water supply in the area, road condition. The average number of points of entire groups is calculated with the help of weights and benefits. Cost/Benefit ratio analysed for each rural road are then ranked as per ascending order of it. This will conclude remarks for the improvement of rural road network for sustainable socio-economic development of Kaski district whose satisfactory results are still to be obtained.